Hambatan Psikolinguistik dalam Pembelajaran Bahasa Arab - Muh Khulaifil Abror; Wulan Indah Fatimatul Djamilah (Lisanuna: Jurnal Ilmu Bahasa Arab dan Pembelajarannya)
The purpose of this study is to present a comprehensive understanding of the various psycholinguistic barriers that learners face in the process of learning Arabic. The research not only aims to identify and analyze the factors that act as barriers, but also to investigate how psycholinguistic approaches can contribute significantly to overcoming these challenges. By exploring the interaction between psychological and linguistic aspects, this research is expected to provide deeper insights into effective ways of creating a learning environment that supports and facilitates the acquisition of Arabic as a second language. Through this approach, it is hoped that strategies can be found that can increase learner confidence and reduce anxiety that often hinders the learning process. The research method used in writing this article is library research, which is an approach that aims to standardize, compile, analyze, and synthesize information through a thorough examination of various relevant literature sources. the results of the study reveal that these barriers significantly reduce learners' active participation and learning effectiveness. The implications of this research include proposing learning strategies that can create a more engaging learning environment.